Unlocking Africa's business potential : trends, opportunities, risks, and strategies - Signé, Landry (Brookings Institution Press, 2020)
"Africa has tremendous economic potential and offers rewarding opportunities for global businesses looking for new markets and long-term investments with favorable returns. Africa has been one of the world's fastest-growing regions over the past decade, and by 2030 will be home to nearly 1.7 billion people and an estimated $6.7 trillion worth of consumer and business spending. Increased political stability in recent years and improving regional integration are making market access easier, and business expansion will create jobs for women and youth, who represent the vast majority of the population. Current economic growth and poverty-alleviation efforts mean that more than 43 percent of the continent's people will reach middle- or upper-class status by 2030. The author examines business opportunities in the eight sectors with the highest potential returns on private investment, the same sectors that will foster economic growth and diversification, job creation, and improved general welfare. These sectors include: consumer markets, agriculture and agri-processing, information and communication technology, manufacturing, oil and gas, tourism, banking, and infrastructure and construction. The book's analysis of these sectors is based on case studies that identify specific opportunities for investment and growth, along with long-term market projections to inform decisionmaking. The book identifies potential risks to business and offers mitigation strategies. It also provides policymakers with solutions to attract new business investments, including how to remove barriers to business and accelerate development of the private sector"--